Perceptions of Postbasic Nursing Students in the Use of Seminars as a Teaching Method - M Chabeli (AOSIS, 1999)
With the transformation of education inthe country, and the outcomes-basededucation that is learner-centred fastgaining ground, nurse educators needto revisit the teaching methods and considerthose that will foster reflective thinkingthrough interactive constructingprocess. These methods, according toCropley and Dave (1978:196) preparelearners for lifelong learning and to challengeproblems in the working world.